CARTAS DE RECOMENDACIÓN EN CICERÓN. EPIST. XIII - Álvarez Suárez, María Paz (Myrtia, 1993)
The writing of the 'litterae commendationis', nearly as old as the written communication, was a deeply rooted practice among the Romans; for this reason, one of the most influential and better known characters of his times in Rome, Cicero, has dealt with a large number of this particular type of letter. Friendship, the reason for this epistolary interchange, gains a special importance in these letters since the absence of such a feeling could make a letter of recommendation ineffective. It is precisely taking into account this feeling of friendship how people who made contact through Cicero are looked at in the writing of these 'epistolae'. Cicero didn't forget a whole epistolary tradition previous to him. However, after the study of the characteristics, the structure and the lexicon, one can conclude that our author covers a cold and academic epistolary with a personal and individual tone together with an admirable management of the Latin language. All this makes the ciceronian 'litterae commendaticiae' appear as a human product elaborated with the best artistic prose.